2003
DOI: 10.1021/es0348750
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Heavy Metals from Soils Using Biodegradable Chelating Agents

Abstract: Metal pollution of soils is widespread across the globe, and the clean up of these soils is a difficulttask. One possible remediation technique is ex-situ soil washing using chelating agents. Ethylenediaminetetraacetic acid (EDTA) is a very effective chelating agent for this purpose but has the disadvantage that it is quite persistent in the environment due to its low biodegradability. The aim of our work was to investigate the biodegradable chelating agents [S,S]-ethylenediaminedisuccinic acid (EDDS), iminodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
278
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(312 citation statements)
references
References 36 publications
24
278
1
9
Order By: Relevance
“…In the EDTA treatments, the concentrations of Pb in the shoots of corn and beans reached up to 270 and 487 mg kg -1 DW, which was 3 and 1.6 times higher than the levels achieved with the EDDS treatments. EDDS has a relatively lower chemical affinity for Pb (log K s = 12.7) (Tandy et al, 2004). Citric acid has a low chemical affinity for Pb (log K s = 6.5) and is easily biodegradable in soil (Römkens et al, 2002), leading to lower effectiveness in increasing concentrations of Pb in shoots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the EDTA treatments, the concentrations of Pb in the shoots of corn and beans reached up to 270 and 487 mg kg -1 DW, which was 3 and 1.6 times higher than the levels achieved with the EDDS treatments. EDDS has a relatively lower chemical affinity for Pb (log K s = 12.7) (Tandy et al, 2004). Citric acid has a low chemical affinity for Pb (log K s = 6.5) and is easily biodegradable in soil (Römkens et al, 2002), leading to lower effectiveness in increasing concentrations of Pb in shoots.…”
Section: Discussionmentioning
confidence: 99%
“…These chelating agents included EDTA (Wu et al, 1999;Lombi et al, 2001), EDDS (log Ks = 18.4, Tandy et al, 2004), EGTA (Römkens et al, 2002), HBED (Wu et al, 1999), and NTA (Kulli et al, 1999;Kayser et al, 2000). However, the chelateenhanced Cu uptake by plant shoots was generally minimal (Kulli et al, 1999;Wu et al, 1999;Kayser et al, 2000;Lombi et al, 2001;Römkens et al, 2002) except for the result reported by Blaylock et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, such an effect may be suppressed at the high temperature and/or at a pressure-persuaded condition due to the higher dissolution proclivity of indium, or lesser rate of re-sorption of the ML complexes in the active surface sites of the solid matrix, etc. [20,36].…”
Section: Extraction Behavior Of the Chelants Under The Influence Of Mmentioning
confidence: 99%
“…However, the steric hindrance between DTPA and dissolved metals might play an important role in the mixed matrix solution. A slower rate of interaction between DTPA and the target metal species irrespective of the temperature conditions or at neutral pH can thereby be assumed [18,20]. The lower pH of EDTA in solution is also mentioned as a reason for the lesser metal extraction capability of DTPA than the EDTA [37].…”
Section: Extraction Behavior Of the Chelants Under The Influence Of Mmentioning
confidence: 99%
See 1 more Smart Citation